Indoor Radio Propagation Measurements in Different Environments Using Two Types of Transmitting Antenna - A. Ameen, Loukman (1997)
The tremendous growth in Wireless Communications System has greatly increased the need to improve the accuracy of predicting signal propagation. It is important to have a tool that can be used to predict the signal coverage area, a method to determine the path loss in microcells, the attenuation due to different partitions and the effect of the environments. To understand radio propagation characteristics in buildings for Personal Communication Systems (PCSs), a comprehensive measurement was carried out in a shopping and business complex, The Mall, in Kuala Lumpur. Two types of Base Station (BS) antennas, Omni-directional and Panel antenna, were mounted on the ceiling and wall respectively. The Mobile Station (MS) uses an antenna with 3dB gain, height 0.5 m and 1.2 m respectively, at 935 MHz carrier frequency. Many test settings were chosen in the office, on the floor sharing with the atrium, lower ground floor and car park, with Line-of-Sight (LOS) and without LOS. The results show some variations of signal strengths with distance that have distinct near and far field regions. The buildings where the measurements were carried out typically have walls and columns constructed from concrete blocks. Within the building the time spread of arriving radio signals depends on reflections and scattering from the structure of the buildings. The results of these measurements are presented and discussed in order to investigate penetration losses in walls, soft boards and floors. The results showed that shadowing due to the objects has a greater influence on the signal strength than the distance between the transmitting and receiving antenna. The path loss within a building is linearly dependent on the logarithm of the distance, on the number of obstacles blocking the signal, on the number of walls between transmitter and receiver antenna, and on the number of floors vertically between the transmitter and receiver antennas. Another important factor is the type of the environment it is operating in, which is given as the factor n. Comparisons between predicted and measured results have shown that the model is capable of predicting the attenuation within the building for different environment.